PEMANFAATAN GOOGLE MAPS DALAM MEMPROMOSIKAN OBJEK WISATA TEBING MAKARIKI NEGERI YAPUTIH KECAMATAN TEHORU KABUPATEN MALUKU TENGAH - Rahmawati Walalayo; Evandro A.W. Manuputty; August J.R. Ufie (Jurnal Administrasi Terapan, 2022)
Makariki Cliffs tourism object is managed by Pokdarwis and has promoted Makariki Cliffs through Facebook and Instagram. But until now, Makariki Cliff has not been "found" on Google Maps. This research is an applied research, using a case study type, and the object of this research is the object of Makariki Cliff Tourism in Yaputih State, Tehoru District, Central Maluku Regency. Based on these results, it can be concluded that the Google Maps application is an application that can assist in promoting the Makariki Cliff Tourism Object, Yaputih State, Tehoru District, Central Maluku Regency, Google Maps can make it easier for visitors to find the location of tourist attractions. In the Google Maps application we can assess visitor satisfaction by using a feature from Google Maps, namely google review. Keywords: Google Maps, attraction, tourist attraction